IDENTIFIKASI DAN PEMETAAN DAERAH BENCANA RAWAN LONGSOR DI KECAMATAN AMARASI BARAT DENGAN MENGGUNAKAN ARC VIEW GIS - Mika Sampe Rompon; Ahmad Almulqu (Politeknik Pertanian Negeri Kupang, 2018)
Land degradation in the western Amarasi causes direct and indirect losses to agricultural land and economic activities of the communities. This study objectivesof this study are to identify the causal factors associated with disaster-prone landslides and to map the vulnerability level of landslides inthe area. In doing so, we require rapid and accurate identification and mapping of the overall disaster location. The Arc View GIS (Geographic Information System) was used to identify the leading causes of landslides, vulnerable areas classification, map digitalization processes, and carry out overlay. The results show that the physical parameters of the causes of landslide-prone areas in the western Amarasi region are rainfall, soil type, slope, and land use. The level of a medium vulnerable landslide is around 9,095.99 ha (55.76%), and not prone around 7,216.94 ha (44.24%) of the total area in western Amarasi.